Low threshold voltage vertical cavity surface-emitting laser - Chalmers, S. A., author; Lear, Kevin L., author; Killeen, K. P., author; IEE, publisher (Colorado State University. Libraries, 1993)
Vertical-cavity surface emitting laser diodes with threshold voltages as low as 1•48 V are demonstrated. The devices have low-resistance epitaxial mirrors, and current passes through the entire mirror stack. The low threshold voltage results from both low threshold current densities and mirrors with low resistivities even at low current densities. The laser fabrication sequence is relatively quick and simple and allows for the rapid characterization of vertical-cavity surface-emittin glaser material.
Keywords: lasers; semiconductor lasers